Vitamin D status in Mexican women at reproductive age, Ensanut 2018-19 - Alejandra Contreras-Manzano; Fabiola Mejía-Rodríguez; Salvador Villalpando; Rosario Rebollar; Mario Flores-Aldana (Instituto Nacional de Salud Pública, 2021)
Objective. To describe the prevalence of deficiency (VDD) and insufficiency (VDI) of vitamin D (VD), by sociodemographic factors, obesity and physical activity in a probabilistic sample of Mexican women participating in Ensanut 2018-19. Materials and methods. In 1 262 women aged 20 to 49 years, the prevalence of VDD/IVD was estimated and the factors associated with it were evaluated with a multinomial regression model. Results. The prevalence of VDI was 46.1% and of VDD was 31.6%. The probability of presenting VDI and VDD was higher for residents of urban areas, in tertiles 2 and 3 of socioeconomic status, and with obesity, while was lower in women with moderate physical activity. Conclusion. The prevalence of vitamin D in Mexican women continues to be a public health problem in Mexico despite the high availability of sunlight in the country. It is necessary to promote healthy sun exposure in the population and consider fortifying foods with vitamin D.